Abnormal Serum Bilirubin/Albumin Concentrations in Dementia Patients With Aβ Deposition and the Benefit of Intravenous Albumin Infusion for Alzheimer’s Disease Treatment - Zhong, Xiaomei; Liao, Yuning; Chen, Xinru; Mai, Naikeng; Ouyang, Cong; Chen, Ben; Zhang, Min; Peng, Qi; Liang, Wanyuan; Zhang, Weiru; Wu, Zhangying; Huang, Xingxiao; et al. (Frontiers in Neuroscience, 2020)
Background: Our previous study in animal models revealed that bilirubin could induce Aβ formation and deposition. Bilirubin may be important in neurodegenerative dementia with Aβ deposition. Hence, lowering the concentration of the free bilirubin capable of crossing the blood brain barrier may benefit the treatment of Alzheimer’s disease (AD). Objectives: To examine changes in the serum bilirubin and albumin concentrations of dementia patients with Aβ deposition, and determine the effects of intravenous administration of albumin in the treatment of AD. Methods: Bilirubin and albumin concentrations in dementia patients with Aβ deposition were examined. Cell viability and apoptosis were determined in dopaminergic neuron-like cells MN9D treated with bilirubin in the presence of diverse concentrations of serum. Human albumin at a dose of 10 g every 2 weeks for 24 weeks was administered intravenously to AD patients to examine the effect of albumin on AD symptoms. Results: Significantly higher indirect bilirubin (IBIL) concentrations, lower albumin concentrations and higher ratio of IBIL to albumin (IBIL/ALB) were observed in dementia patients with Aβ deposition, including AD, dementia with Lewy bodies and general paresis of insane. In vitro assays showed that bilirubin-induced injury in cultured dopaminergic neuron-like cells negatively depends on the concentration of serum in the culture medium. General linear model with repeated measures analysis indicated a main effect of group on the change in Alzheimer’s Disease Cooperative Study Activities of Daily Living Inventory scale (ADCS-ADL) scores, and main effect of time and group, and group-by-time interaction on the change of Clinical Dementia Rating Scale–Sum of Boxes (CDR-SB) scores. Analysis of the combined data of the entire 28 weeks of assessment period using the area under curve convincingly showed significantly improvements in change of ADCS-ADL scores and CDR-SB scores. Conclusions: IBIL and the IBIL/ALB ratio are significantly higher in dementia patients with Aβ deposition and intravenous administration of albumin is beneficial to AD treatment. Trial registration: The intervention study was registered at http://www.chictr.org.cn (ChiCTR-IOR-17011539). Date of registration: June 1, 2017.